Factores que influyen en la percepción de servicios de los ecosistemas para el desarrollo ecoturístico del humedal La Tembladera - Cartuche Paqui, David Vladimir (2018)
The conservation of ecosystem services is today one of the main challenges in terms of Environmental Management. The province of "El Oro" is benefited with wetland ecosystems that enrich its biodiversity, as is the case of "La Tembladera" located in the canton of Santa Rosa. However, these places have been poorly researched, so it is difficult to determine their impact on the local population, that is, how the regulation, support and maintenance services work and in what sense the locality she looks affected. Therefore, the present investigation aims to determine what factors of the ecosystem services in the case of the La Tembladera wetland influence the perception of the inhabitants of the nearby communities. For this research we chose the methodology with a qualitative and quantitative approach, making use of descriptive statistics, which results in a strong tendency to promote tourism and recreation in the locality.